Modern air, englacial and permafrost temperatures at high altitude on Mt Ortles (3905 m a.s.l.), in the eastern European Alps - Carturan, Luca; De Blasi, Fabrizio; Dinale, Roberto; Dragà, Gianfranco; Gabrielli, Paolo; Mair, Volkmar; Seppi, Roberto; Tonidandel, David; Zanoner, Thomas; Zendrini, Tiziana Lazzarina; Dalla Fontana, Giancarlo (Earth System Science Data, 2023)
The climatic response of mountain permafrost and glaciers located in high-elevation mountain areas has major implications for the stability of mountain slopes and related geomorphological hazards, water storage and supply, and preservation of palaeoclimatic archives. Despite a good knowledge of physical processes that govern the climatic response of mountain permafrost and glaciers, there is a lack of observational datasets from summit areas. This represents a crucial gap in knowledge and a serious limit for model-based projections of future behaviour of permafrost and glaciers. A new observational dataset is available for the summit area of Mt Ortles, which is the highest summit of South Tyrol, Italy. This paper presents a series of air, englacial, soil surface and rock wall temperatures collected between 2010 and 2016. Details are provided regarding instrument types and characteristics, field methods, and data quality control and assessment. The obtained data series are available through an open data repository (https://doi.org/10.5281/zenodo.8330289, Carturan et al., 2023). In the observed period, the mean annual air temperature at 3830 m a.s.l. was between -7.8 and -8.6 C-degrees. The most shallow layers of snow and firn (down to a depth of about 10 m) froze during winter. However, melt water percolation restored isothermal conditions during the ablation season, and the entire firn layer was found at the melting pressure point. Glacier ice is cold, but only from about 30 m depth. Englacial temperature decreases with depth, reaching a minimum of almost -3 C-degrees close to the bedrock, at 75 m depth. A small glacier located at 3470 m a.s.l., close to the summit of Mt Ortles, was also found in cold conditions down to a depth of 9.5 m. The mean annual ground surface temperature was negative for all but one monitored sites, indicating cold ground conditions and the existence of permafrost in nearly all debris-mantled slopes of the summit. Similarly, the mean annual rock wall temperature was negative at most ...